Digital Library System Development To Improve The Ten Top Skills Of Biology Education Students - Ekariana S. Pandia; Siska Rita Mahyuny; Teuku Hadi Wibowo Atmaja (Postgraduate, University of Mataram, 2022)
Library as a storage room books that are kept on a regular basis to be read and studied or used as reference material. Advances in digital technology have changed many things, one of which is in the world of education where technology is used in the library field which can build many skills. Advances in technology advances in digital technology are utilized in the field of libraries which can build many skills. In developing skills, the top ten skills include Cognitive Flexibility. Cognitive Flexibility is the ability to think and align cognitive strategy processes in dealing with new and unexpected situations. The research method used is Research and Development with a 4D model approach. The subjects in this study were students of Biology Education, Faculty of Teacher Training and Education, Samudra University in semesters V and VII. The results of the digital library IT expert validation test where Accessibility has a score of 92%, while the lowest, navigability and copyright have a score of 50%. While the validation of the librarian's ease of reading and storing has 88% while the inventory suitability is 50%. While the practicality test for users is 75%. This is because there is still a need for more in-depth development in increasing the collection of various books in the Biology education study program at Samudra University